Analisis sarana dan prasarana di SD INPRES VI kalabahi tengah - Kristi Adelia Waang; Jhon Abraham Lalang Yame; Dorce Laure; Kasianus Malaikalong; Julianan Aplianti Pelang (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
This research focuses on analyzing the facilities and infrastructure at SD Inpres Kalabahi Tengah. The study aims to evaluate the quality, management, and effectiveness of the school’s facilities in supporting educational activities. The results indicate that the planning of facilities and infrastructure at SD Inpres VI Central Kalabahi is relatively good, reflecting a well-thought-out strategy to meet students’ learning needs. However, the procurement process of these facilities and infrastructure still requires significant improvements to ensure that all necessary resources are available and maintained adequately. Furthermore, the study reveals that the management and utilization of the school’s facilities are not yet optimal, which affects the overall effectiveness of learning processes. Inefficiencies in maintenance, allocation, and supervision were identified as key challenges that need to be addressed. Based on these findings, the research provides practical recommendations for enhancing the quality of school facilities and infrastructure. These recommendations include systematic planning, regular evaluation, proper maintenance, and allocation of resources to ensure that facilities fully support effective and efficient learning activities. Improving these aspects is expected to create a more conducive learning environment, increase student engagement, and support teachers in delivering quality education. This study contributes valuable insights for school administrators, educational policymakers, and stakeholders in planning and managing educational facilities to achieve better academic outcomes